Impact of high on-treatment platelet reactivity after angioplasty in patients with peripheral arterial disease. (3rd April 2021) - Busch, Lucas; Stern, Manuel; Dannenberg, Lisa; Mourikis, Philipp; Gröne, Michael; Özaslan, Göksen; Heinen, Yvonne; Heiss, Christian; Sansone, Roberto; Polzin, Amin; Kelm, Malte
Abstract: Objective : High on-treatment platelet reactivity (HTPR) to dual antiplatelet therapy (DAPT) predicts adverse events in coronary artery disease patients. In peripheral artery disease (PAD) patients, data concerning the clinical impact of HTPR are limited. Therefore, we evaluated the incidence of (i) HTPR to DAPT and (ii) its impact on 6 months outcome after angioplasty. Methods and results : In this prospective single center analysis, we investigated 102 consecutive patients with PAD from 2016 to 2017. All patients underwent peripheral endovascular treatment due to intermittent claudication (Fontaine IIb). Clopidogrel effects were measured using vasodilator-stimulated protein phosphorylation (VASP) assay, aspirin effects by light-transmission aggregometry (LTA). Major adverse limb events (MALE), major adverse cardiac and cerebrovascular events (MACCE) and BARC bleeding (bleeding academic research consortium classification) within 6 months were assessed. HTPR to clopidogrel (n = 37, 36%), to aspirin (n = 11, 11%) and to both (n = 11, 11%) were frequent. Compared to sufficient platelet inhibition by aspirin and clopidogrel (n = 43, 42%), patients with dual HTPR showed a higher risk of MALE at 6 months (27% vs. 7%; hazard ratio [HR]: 4.45; 95% confidence interval [CI]: 1.1 to 67.8; p = .03). This was independent of diabetes, creatinine, body mass index, and age as well as of procedural details in a multivariate logistic regression analysis. MACCE (n = 2) and BARC bleeding rates (n = 2) were low. Conclusion : In this small exploratory study, HTPR was frequent in PAD patients. Furthermore, the results are suggestive that MALE might be associated with dual HTPR. This leads to the hypothesis that optimized antithrombotic regimens post percutaneous transluminal angioplasty should be tested in clinical trials.